Variation in population density of the Andean night monkey (Aotus lemurinus) in areas with different landscape characteristics - Chica Flórez, Laura; Roncancio Duque, Néstor; Solari, Sergio (THERYA, 2022)
In the Colombian Andes, most of the populations of Andean night monkeys (Aotus lemurinus) are found in fragmented landscapes due to the predominant changes in land use in the region. Thus, forest fragments differ in shape, size, degree of isolation, and availability of resources. These factors have had a differential effect on the ecology and permanence of their populations. In order to determine the effect of fragmentation on A. lemurinus, we estimated its population density in a protected area of 489 ha of sub-Andean forest - at Otún Quimbaya Wildlife Sanctuary- which is structurally connected with other protected areas; then, we compared it with another study carried out in the unprotected Sub-andean forest fragments (900 ha) of Dapa, at the Valle del Cauca department. To estimate its density, the distance sampling method was used with 31 linear transects, and the data were analyzed with the software Distance. Landscape metrics was estimate with patch analyses tools with a Corine Land Cover information 1:100,000 scale. The plant structure and diversity were measurement with transects to 50 x 4 m and taking account the trees with diameter at breast height over 10 cm. We use average comparison to evaluate the similarities between patrons of the population density and explanatory variables. A population density of 39 ind/km2 was found in our study, which is lower than the 113 ind/km2 found in the Dapa. This relation was similar to relations of mean shape index, mean patch size and mean diameter at breast height, and inverse with the relations of proportion of the forest in the area, weighted cover index, plant diversity and density of trees. It is likely that the protected area, by being connected and having a greater diversity of primates and trees, allows this population not to suffer from a crowding phenomenon, and that the population does not increase it carrying capacity due to the low presence of competing species, conversely to what could be occurring in the unprotected fragments. Conversely, high density in Dapa could be reflect a system depletion in diversity and ecological processes.